Dry coating of solid dosage forms: an overview of processes and applications. (2nd December 2017) - Foppoli, Anastasia Anna; Maroni, Alessandra; Cerea, Matteo; Zema, Lucia; Gazzaniga, Andrea
Abstract: Dry coating techniques enable manufacturing of coated solid dosage forms with no, or very limited, use of solvents. As a result, major drawbacks associated with both organic solvents and aqueous coating systems can be overcome, such as toxicological, environmental, and safety-related issues on the one hand as well as costly drying phases and impaired product stability on the other. The considerable advantages related to solventless coating has been prompting a strong research interest in this field of pharmaceutics. In the article, processes and applications relevant to techniques intended for dry coating are analyzed and reviewed. Based on the physical state of the coat-forming agents, liquid- and solid-based techniques are distinguished. The former include hot-melt coating and coating by photocuring, while the latter encompass press coating and powder coating. Moreover, solventless techniques, such as injection molding and three-dimensional printing by fused deposition modeling, which are not purposely conceived for coating, are also discussed in that they would open new perspectives in the manufacturing of coated-like dosage forms.